Aksi Bersama Cegah Stunting Melalui Kuliah Kerja Nyata di Kabupaten Gowa - Muhammad Rachmat; Citrakesumasari Citrakesumasari; Gandi Gandi; Nasrah Nasrah; Muhammad Kurnia (Pusat Penelitian & Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2023)
The stunting locus village in Gowa Regency, South Sulawesi, has become the location of the Real Work Lecture on Community Learning and Empowerment of Hasanuddin University (KKN-PPMUH) program. The program aimed to empower society by enhancing knowledge, strengthening intentions and skills. The program focused on the stunting prevention behaviors of pregnant women, breastfeeding women, toddler moms, young women, elementary school students, and health cadres. The methods of KKN-PPMUH activities included health counseling, trainings, simulations, practices, and social mapping of the stunting prevention targets. This program was conducted in July to August 2022 in the villages of Pakatto, Je'nemadinging, Pacellekang, and Panaikang. The KKN-PPMUH consisted of stages such as program preparation, implementation, monitoring, evaluation, and program reporting. Pre-test and post-test questionnaires are used to evaluate the activities. Based on the results of KKN-PPMUH activities, there was an increase in knowledge and reinforcement of intentions and skills on targets, particularly those about anemia in young women and pregnant women, exclusive breastfeeding in breastfeeding women, innovation of weaning food (MP-ASI) and stunting prevention food on toddler moms, the behavior of a clean and healthy life (PHBS) in elementary school students, and interpersonal communication (KAP) on posyandu cadres. Besides that, both the fish farming in buckets (Budikdamber) and the planting of moringa activities were done properly. The Stunting Thematic KKN-PPMUH activities in Gowa Regency have enhanced the knowledge and reinforced the intentions and skills of the targets. The stunting prevention programs in the stunting locus villages should be conducted continuously by doing university partnership work in their area